2010
DOI: 10.34101/actaagrar/i/8371
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous salicylic acid treatments enhance tolerance to salinity of wheat (Triticum aestivum) plantlets

Abstract: Salt stress, an abiotic stress, determines modifications of some biochemical indicators, like, antioxidant enzymes, proline (amino acidaccumulate in higher plants under salinity stress) content, and some physiological processes including: plant growth and development. Inthis paper we studied the influence of exogenous treatment of wheat seeds, with 0.1 mM salicylic acid (SA) solution, in the plant response tosalt stress. The treatment was applied by presoaking the seeds in the treatment solution for 12 hours b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Salicylic acid (SA) plays an important role in regulating plant growth, production, maturation, and defense responses ( Miura and Tada, 2014 ). For instance, SA significantly increased seedling size and mass compared to the untreated (control) when applied exogenously to wheat seedlings ( Purcǎrea et al, 2010 ), and high salt tolerance of wheat seedlings was observed when treated with the SA solution ( Cornelia et al, 2011 ). The application of SA as a soil drench stimulates antioxidant protective responses that may lead to systemic acquired resistance (SAR) resulting in F. pseudograminearum ( Sorahinobar et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Salicylic acid (SA) plays an important role in regulating plant growth, production, maturation, and defense responses ( Miura and Tada, 2014 ). For instance, SA significantly increased seedling size and mass compared to the untreated (control) when applied exogenously to wheat seedlings ( Purcǎrea et al, 2010 ), and high salt tolerance of wheat seedlings was observed when treated with the SA solution ( Cornelia et al, 2011 ). The application of SA as a soil drench stimulates antioxidant protective responses that may lead to systemic acquired resistance (SAR) resulting in F. pseudograminearum ( Sorahinobar et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous salicylic acid exhibits a good impact on these parameters, reducing the negative effects of water deficiency on plants while considerably reducing the water loss rate and chlorophyll content under drought stress (Purcarea et al. 2010 ). SA plays an important role in enhancing drought stress tolerance.…”
Section: Discussionmentioning
confidence: 99%